2022
DOI: 10.3389/fphar.2022.838599
|View full text |Cite
|
Sign up to set email alerts
|

Physiologically based pharmacokinetic modeling of daptomycin dose optimization in pediatric patients with renal impairment

Abstract: Background and Objective: Daptomycin is used to treat Gram-positive infections in adults and children and its dosing varies among different age groups. We focused on the pharmacokinetics of daptomycin in children with renal impairment, which has not been evaluated.Methods: A physiologically based pharmacokinetic (PBPK) model of daptomycin was established and validated to simulate its disposition in healthy populations and adults with renal impairment, along with a daptomycin exposure simulated in pediatric pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 54 publications
1
4
0
Order By: Relevance
“…Therefore, taking into account the low chance of toxicity related to high doses, we assume that the suggested GFR-adjusted dosages for children with CKD are adequate. Additionally, the AUC 0–24h ratio (CKD/non-CKD) was similar across all age groups for 3TC and FTC, in accordance with other PBPK studies that have examined renally excreted drugs in children with CKD [ 39 , 43 ]. Furthermore, a population PK study found a comparable effect of kidney function reduction on the clearance of ceftriaxone for children versus adults, a renally excreted antibiotic drug [ 44 ].…”
Section: Discussionsupporting
confidence: 88%
“…Therefore, taking into account the low chance of toxicity related to high doses, we assume that the suggested GFR-adjusted dosages for children with CKD are adequate. Additionally, the AUC 0–24h ratio (CKD/non-CKD) was similar across all age groups for 3TC and FTC, in accordance with other PBPK studies that have examined renally excreted drugs in children with CKD [ 39 , 43 ]. Furthermore, a population PK study found a comparable effect of kidney function reduction on the clearance of ceftriaxone for children versus adults, a renally excreted antibiotic drug [ 44 ].…”
Section: Discussionsupporting
confidence: 88%
“…Lingling Ye et al established a PBPK model of daptomycin to simulate its disposition in healthy populations and adults with renal impairment using GrastroPlus (version 9.7), along with a daptomycin exposure simulated in pediatric patients with renal impairment. Their model may be a valuable tool for predicting the PKs of daptomycin and supporting dose adjustments or other relevant decisions in clinical settings 53 . Another study investigated the PK of apixaban alone and under the influence of interacting drugs.…”
Section: Resultsmentioning
confidence: 99%
“…Verified PBPK models of drugs are presented in support of pediatric dose prediction (Figure 4 ): 13 articles reported results from P‐PBPK models, which are presented in support of dose selection, 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 five articles were on the optimization of dosage in the design of future pediatric clinical studies, 3 , 29 , 43 , 44 , 45 and six articles reported findings from studies on determining dose regimens. 46 , 47 , 48 , 49 , 50 , 51 Fourteen publications were on some special pediatric populations and uncommon diseases with an assessment of renal impairment, 52 , 53 , 54 , 55 , 56 children with obesity, 57 , 58 , 59 , 60 and pediatric patients with severe coronavirus disease 2019 (COVID‐19) disease. 61 , 62 , 63 , 64 , 65 Consistent with this trend, several big research funding/grants for computational pharmaceutics worldwide were launched (Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In adults PPB is between 90–94%, it does not depend on concentration, but is decreased with decreasing renal function [ 167 ]. The clinical significance of this fact is discussible, in the study of physiologically based pharmacokinetic modeling of daptomycin dose optimization in pediatric patients with renal impairment no dose adjustment was proposed for patients with mild-to-moderate renal impairment, and only for severe cases was a dose decrease recommended [ 168 ].…”
Section: General Considerations On Neonate’s Pharmacokineticsmentioning
confidence: 99%